Use of a Hooked Cutting Device Compared With Scissors for the Emergency Exposure of Critically Ill and Injured Patients. Issue 1 (13th December 2013) - Tang, Nelson; Levy, Matthew J.; Harrow, Jeffrey; Bingham, Nina
Abstract: Introduction: The initial assessment of critical patients includes prompt identification of life-threatening conditions. Any device or technique that can aid in this process may ultimately save lives. This study examined whether clothing could be removed faster with the use of a hooked cutting device as compared with the commonly-used heavy-duty, blunt-tipped, serrated scissors. Methods: This study took place in an urban academic emergency department of a Level-1 trauma center. Human patient simulator mannequins were clothed in identical shirts and pants. The time required for clinical personnel to expose the patient using each device was measured. Each of the 50 participants was queried regarding their tactile comfort using each device. Results: The mean time for shirt removal using scissors was 83 seconds (SD = 55 seconds; 95% CI, 68-99). The mean time for shirt removal using the hook device was 28 seconds (SD = 21 seconds; 95% CI, 22-34). The mean time for pants removal using scissors was 69 seconds (SD = 40 seconds; 95% CI, 56-73). The mean time for pants removal using the hook device was 19 seconds (SD=15 seconds; 95% CI, 15-23). Conclusions: The hooked device was 69% faster at removing clothing than traditionally-used scissors. Though simple in concept, these implications can be life saving, particularly in conditions of uncontrolled, life-threatening external hemorrhage. N Tang, M Levy, J Harrow, N Bingham .Use of a hooked cutting device compared with scissors for the emergency exposure of critically ill and injured patients .Prehosp Disaster Med .2013 ;28 (6 ):1 -4 .